2006
DOI: 10.1007/s00216-006-0728-3
|View full text |Cite
|
Sign up to set email alerts
|

Analytical methods for the determination of persistent ingredients of personal care products in environmental matrices

Abstract: Concern about the environmental fate and potential effects of synthetic organic chemicals used in soaps, lotions, toothpaste, and other personal care products continues to increase. This review describes procedures used for the analysis of five classes of these compounds-synthetic musk fragrances, antimicrobials, ultraviolet filters, insect repellents, and parabens-in water, sediment, sewage sludge, air, and aquatic biota. The primary focus is on sample extraction and preparation methods for these compounds. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
85
0
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 238 publications
(90 citation statements)
references
References 156 publications
2
85
0
3
Order By: Relevance
“…A comparison of the recovery values obtained with Strata-X and C 18 showed that the former was clearly superior due its ability to adsorb polar and apolar moieties present in the PCP molecules [8,22,24].…”
Section: Strata-x Sorbentmentioning
confidence: 99%
See 4 more Smart Citations
“…A comparison of the recovery values obtained with Strata-X and C 18 showed that the former was clearly superior due its ability to adsorb polar and apolar moieties present in the PCP molecules [8,22,24].…”
Section: Strata-x Sorbentmentioning
confidence: 99%
“…Previous studies showed that some volatile compounds could be lost in the evaporation step and thus result in very low (a 30%) recovery [8].…”
Section: The Effect Of Evaporation Proceduresmentioning
confidence: 99%
See 3 more Smart Citations